Exploring the implication of communal violence on peaceful coexistence and security governance in Bauchi State, Nigeria - Ilelah, Kabiru Bello; Ab Halim, Adlina; Ismail, Mohd Mahadee; Nor, Mohd Sabri (Human Resource Management Academic Research Society, 2024)
Communal violence continues to be a challenge to peaceful coexistence and security governance in Bauchi State as well as to Nigeria's national security. Therefore, this study investigates the implications of the persistence of communal violence in hindering the achievement of peace, stability, and security governance in Bauchi State. Governance theory was used as a framework. An in-depth qualitative case study was used to accomplish the study's objective. A total of 17 informants were interviewed through Zoom video calls. The data are analyzed based on thematic analysis with NVivo 12.0. The findings reveal that the persistence of communal violence has implications for the peaceful coexistence among the people in the state. Such implications include a lack of trust and harmony among the people, loss of lives, and property destruction. The study recommends the provision of mechanisms that can enhance the monitoring of security in the communities of the state. The study can immensely contribute to policymaking, as it will aid policymakers in providing alternative strategies to enhance security governance in the state and the country. It will further serve as reference material for researchers. Therefore, this study highlights the significant implications of communal violence affecting peaceful coexistence and security governance.